OpenOpticalFlow: An Open Source Program for Extraction of Velocity Fields from Flow Visualization Images. Issue 1 (20th October 2017) - Liu, Tianshu
This paper describes OpenOpticalFlow, an open source optical flow program in Matlab for extraction of high-resolution velocity fields from various flow visualization images. This program is a useful tool for researchers to use the optical flow method in various flow measurements. The principles of the optical flow method are concisely described, including the physics-based optical flow equation, the variational solution, and errors. The central part of this paper is the descriptions of the main program, relevant subroutines and selection of the relevant parameters in optical flow computation. Examples are given to demonstrate the applications of the optical flow method.